Evaluation of Sesame Genotypes for Powdery Mildew Resistance - Rao, P. Venkata Ramana; Shankar, V. Gouri; Pavani, J. V. P.; Rajesh, V.; Reddy, A. Vishnuvardhan; Reddy, K. Dharma (International Journal of Bio-resource and Stress Management, 2011)
Powdery mildew is a devastating disease in Sesame throughout India, causing considerable yield loss. Use of host plant resistance is the cheapest and effective disease management strategy. In the present investigation 37 genotypes along with a susceptible check Swethatil were screened against powdery mildew under natural conditions during rabi, 2010-11. Twenty four genotypes showed susceptible and 11 showed tolerant reaction. Only three genotypes (TKG-22, NSKMS-260 and G-55) showed resistant reaction. None of the genotypes recorded immune response. The resistant genotypes can be utilized in breeding program to evolve resistant varieties.